2019
DOI: 10.4103/jgid.jgid_105_18
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors associated with diarrhea among under-five children in Manado Coastal Area, Indonesia

Abstract: Background:Diarrhea is a condition where individuals experience defecation as much as 3 or more per day with a soft consistency. Diarrhea in children is one of the environmentally-based diseases, and Manado is one of the cities faced with this environmental lead diarrhea problems. The purpose of this study is to analyze the influence of socioeconomic factors on the occurrence of diarrhea among under-five children in the coastal area of Manado city.Materials and Methods:A cross-sectional study design was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
15
0
4
Order By: Relevance
“…In the study, it is evident that daily income has a significant association with diarrhea prevalence, accordingly multivariate logistic regression demonstrated that the children originate from poor daily income family is 4 times more likely to suffer from diarrhea. A study conducted in Manado, Indonesia concluded that socio-economic factors, such as caretaker educational level, family income, and savings level, play roles in affecting diarrhea incidence alongside with other caretaker characteristics [38]. Similarly, first poorest quartile of wealth index almost increases 2 times of diarrhea incidence in a rural region of Tanzania [39].…”
Section: Discussionmentioning
confidence: 99%
“…In the study, it is evident that daily income has a significant association with diarrhea prevalence, accordingly multivariate logistic regression demonstrated that the children originate from poor daily income family is 4 times more likely to suffer from diarrhea. A study conducted in Manado, Indonesia concluded that socio-economic factors, such as caretaker educational level, family income, and savings level, play roles in affecting diarrhea incidence alongside with other caretaker characteristics [38]. Similarly, first poorest quartile of wealth index almost increases 2 times of diarrhea incidence in a rural region of Tanzania [39].…”
Section: Discussionmentioning
confidence: 99%
“…Most occupations of mothers of children under-five are housewives, 33 (89.2%) research subjects. Research by Sumampouw et al (2019) and Santika et al (2020) said that the level of education has a significant effect on diarrhea cases in children under five. The level of education is a major determining factor for the survival of children, especially those under five who cannot carry out activities independently (Omona et al, 2020).…”
Section: Characteristics Of Research Subjectsmentioning
confidence: 99%
“…Diarrhea is the most prevalent pediatric disease and causes of death in children under 5 years-of-age in developing countries. Moreover, diarrheal diseases cause serious economic problems for developing countries (Sumampouw et al, 2019).…”
Section: The Main Causes Of Diarrhea; Infectionmentioning
confidence: 99%